2014
DOI: 10.1159/000366519
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endotoxaemia and Frequent Haemodialysis Schedules

Abstract: Background/Aims: Endotoxaemia, a driver of systemic inflammation, appears to be driven by dialysis-induced circulatory stress in haemodialysis (HD) patients. More frequent HD regimens are associated with lower ultrafiltration requirements, improved haemodynamic stability and lower systemic inflammation. This study investigated the hypothesis that more frequently dialysed patients, with reduced exposure to dialysis-induced haemodynamic perturbation, would have lower circulating endotoxin (ET) levels. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Our results also integrate with the findings by McIntyre and colleagues, who hypothesized that hemodialysis-induced systemic circulatory stress and recurrent bowel ischemia may lead to increased endotoxin translocation from intestine (23,24). Their studies demonstrated that patients on hemodialysis have six-fold higher levels of circulating endotoxin than patients on peritoneal dialysis or with nondialysis-dependent patients with CKD, and that endotoxin levels were higher among patients with more dialysis-induced BP instability (23).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results also integrate with the findings by McIntyre and colleagues, who hypothesized that hemodialysis-induced systemic circulatory stress and recurrent bowel ischemia may lead to increased endotoxin translocation from intestine (23,24). Their studies demonstrated that patients on hemodialysis have six-fold higher levels of circulating endotoxin than patients on peritoneal dialysis or with nondialysis-dependent patients with CKD, and that endotoxin levels were higher among patients with more dialysis-induced BP instability (23).…”
Section: Discussionsupporting
confidence: 90%
“…Their studies demonstrated that patients on hemodialysis have six-fold higher levels of circulating endotoxin than patients on peritoneal dialysis or with nondialysis-dependent patients with CKD, and that endotoxin levels were higher among patients with more dialysis-induced BP instability (23). Conversely, patients who had more frequent hemodialysis and less BP instability had lower circulating endotoxin levels (24).…”
Section: Discussionmentioning
confidence: 99%
“…66 Patients receiving conventional thrice weekly hemodialysis had higher predialysis serum endotoxin level than those receiving short daily hemodialysis or nocturnal hemodialysis, even after adjusting for age and diabetic status. 67 Relation with CVD in CKD Two studies have reported that plasma endotoxin level correlates with ultrafiltration rate in patients on hemodialysis 67 and the drop in systolic BP during hemodialysis treatment. 66 Plasma endotoxin level of patients on hemodialysis also correlates with cardiac troponin T and CRP levels.…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%
“…43, 44 Repetitive insults and stunning may then lead to ventricular remodeling and the effects of heart failure 4446 when ejection fraction declines. This ultrafiltration induce hypotension may also lead to ischemia to other organs including the brain 47 , GI tract 48, 49 and kidney. Intradialytic hypotension with ischemia to the kidney may also be a contributing factor to further loss of residual kidney function 50 which would result in more difficulties with volume management for HD patients.…”
Section: Approach To Fluid Management In Hd Patientsmentioning
confidence: 99%